Paying zakat to non-Muslim and charity organization / Amirah Elyana Shamsuddin … [et al.] - Shamsuddin, Amirah Elyana; Mohamed Shaiful Azam, Nur Fatini; Hasmuni, Nur Hidayah; Mohd Rashdi, Nurul Iffah Atiyah (2023)
Zakat is a maaliyah act of worship that helps Muslims, especially in improving their standard of living. Zakat is also one of the solutions to the problem of poverty. The rich (muzakki) will help the poor (mustahiq) from a financial welfare point of view and attract followers of other religions to embrace Islam and its teachings. Generally, Zakat is the third pillar of Islam. The attitude of giving help and sharing sustenance with fellow Muslims is highly encouraged to strengthen the relationship of brotherhood among Muslims and obtain a great reward from Allah. However, Islam not only focuses on the needs of fellow Muslims but also cares about the needs of other fellow human beings, even if they are non-Muslims and charitable organizations.